Post-treatment material for absorbent article, absorbent article including post-treatment material for absorbent article, and manufacturing method therefor
Patent Information
- Application Number
- JP2022064768
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-04-08
- Publication Date
- 2025-02-10
- Estimated Expiration
- 2042-04-08
AI Technical Summary
Absorbent articles with softer outer packaging materials face issues with insufficient fixation and stability during disposal, leading to potential separation of the post-treatment tape from the exterior body.
A post-treatment material for absorbent articles comprising a nonwoven fabric layer with chemical fibers and a resin layer containing an elastomer, designed with a density of 15 kg/m³ to 120 kg/m³, which can be ultrasonically or thermally welded to the exterior body, providing a strip-shaped structure with folded ends for easy fixation and maintenance of a rolled state.
The solution ensures effective fixation and maintenance of the absorbent article in a rolled state during disposal, offering excellent appearance and feel while reducing the risk of separation from the exterior body.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a post-treatment material for absorbent articles, an absorbent article provided with the post-treatment material for absorbent articles, and a method for manufacturing the same.
Background Art
[0002] Absorbent articles such as diapers and sanitary products generally include an absorbent pad that absorbs and holds excrement and the like discharged by a wearer to the outside of the body, and an outer wrapper that supports the absorbent pad on its inner surface. The used absorbent article is fixed in a rolled-up state with the absorbent pad inside and discarded. As a method for fixing the used absorbent article, it has been proposed to provide a post-treatment tape on the absorbent article. Since the absorbent article directly touches the skin, a softer and more tactile material is used for the outer wrapper. Therefore, a soft and tactile post-treatment tape has been proposed (for example, Patent Document 1). However, in an absorbent article using a softer material as the outer wrapper, it may not be possible to sufficiently fix the used absorbent article. Also, the post-treatment tape itself may not be sufficiently fixed to the outer wrapper. Therefore, there is a need for post-treatment means that can fix and hold the rolled-up state at the time of disposal even for absorbent articles using a soft material for the outer wrapper with a good touch.
Prior Art Documents
Patent Documents
[0003]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0004] The present invention has been made to solve the above conventional problems, and an object thereof is to provide a post-treatment material for absorbent articles that is excellent in appearance and touch and can fix and hold a rolled-up state at the time of disposal.
Means for Solving the Problems
[0005] The post-treatment material for absorbent articles according to the embodiment of the present invention has a density of 15 kg / m³ 3 ~120 kg / m 3 The material comprises a nonwoven fabric layer containing a nonwoven fabric containing chemical fibers, a resin layer containing an elastomer layer, and a joint that is joined to the outer casing of an absorbent article. The nonwoven fabric layer is the outermost surface of the post-treatment material for absorbent articles, and the joint is a portion that can be welded by ultrasonic welding or heat welding. In one embodiment, the nonwoven fabric is a spunlace nonwoven fabric, a carded nonwoven fabric, an air-through nonwoven fabric, or a spunjet nonwoven fabric. In one embodiment, the chemical fiber is an olefin-based resin fiber. In one embodiment, the chemical fiber is a polypropylene resin fiber. In one embodiment, the nonwoven fabric contains 30% by weight or more of polypropylene resin fibers. In one embodiment, the elastomer layer comprises a styrene-based elastomer or an olefin-based elastomer. In one embodiment, the elastomer layer comprises an olefin-based elastomer. In one embodiment, the olefin-based elastomer is a propylene-based elastomer. In one embodiment, the post-treatment material for absorbent articles includes a foldable structure. In one embodiment, the post-treatment material for absorbent articles is in the form of a strip and has a length of 50 mm to 250 mm. In one embodiment, the basis weight of the post-treatment material for absorbent articles is 50 g / m². 2 ~150g / m 2 That is the case. In one embodiment, the elongation at break of the post-treatment material for absorbent articles is 150% to 600%. In one embodiment, the maximum strength of the post-treatment material for absorbent articles is 2N / 10mm or more. In one embodiment, the post-treatment material for absorbent articles has an elongation stress of 0.5 N / 10 mm or more. In one embodiment, the elongation of the post-treatment material for absorbent articles under a 2N load is 30% or more. In another aspect of the embodiments of the present invention, an absorbent article is provided. This absorbent article comprises an outer casing and a post-treatment material for the absorbent article. In one embodiment, the absorbent article has a nonwoven fabric as its outermost surface, and the density of the nonwoven fabric is 15 kg / m³. 3 ~120 kg / m 3 That is the case. In one embodiment, the absorbent article is a pant-type diaper. In another aspect of the embodiments of the present invention, a method for manufacturing an absorbent article is provided. This manufacturing method yields an absorbent article with a density of 15 kg / m³. 3 ~120 kg / m 3 The process involves laminating a nonwoven fabric layer containing chemical fibers and a resin layer containing an elastomer layer to create a laminate, and This includes joining the laminate and the outer casing of the absorbent article by ultrasonic welding or heat welding. [Effects of the Invention]
[0006] According to the present invention, it is possible to provide a post-treatment material for absorbent articles that has excellent appearance and feel, and can fix and maintain a rolled-up state when discarded. [Brief explanation of the drawing]
[0007] [Figure 1] This is a schematic perspective view of an absorbent article equipped with a post-treatment material for absorbent articles according to an embodiment of the present invention. [Figure 2] This is a schematic cross-sectional view of a post-treatment material for absorbent articles according to an embodiment of the present invention. [Figure 3] This is a schematic cross-sectional view showing the form of use of the post-treatment material for absorbent articles according to an embodiment of the present invention. [Figure 4] This is a schematic perspective view showing an absorbent article fixed with a post-treatment material for absorbent articles according to an embodiment of the present invention. [Figure 5] It is a schematic perspective view showing the back surface of an absorbent article fixed by a post-treatment material for absorbent articles shown in FIG. 4.
Embodiments for Carrying out the Invention
[0008] A. Outline of the Post-Treatment Material for Absorbent Articles The post-treatment material for absorbent articles (hereinafter also referred to as "post-treatment material") of the embodiment of the present invention has a density of 15 kg / m 3 ~120 kg / m 3 and includes a non-woven fabric layer containing a non-woven fabric containing chemical fibers, a resin layer containing an elastomer layer, and a joint portion joined to the outer package of the absorbent article. The non-woven fabric layer is the outermost surface of the post-treatment material for absorbent articles. The joint portion is a portion configured to be weldable by ultrasonic welding or heat welding. If the outermost surface of the post-treatment material is a non-woven fabric with a density of 15 kg / m 3 ~120 kg / m 3 it is possible to provide a post-treatment material excellent in appearance and touch. Also, if the joint portion joined to the outer package of the absorbent article is a portion configured to be weldable to the outer package by ultrasonic welding or heat welding, the post-treatment material can be firmly fixed to the absorbent article. The post-treatment material of the embodiment of the present invention is easy to stretch and easy to post-treat during use, and can hold the absorbent article in a rolled-up state, for example, after being fixed. The post-treatment material of the embodiment of the present invention is typically in a strip shape. For example, the joint portions are provided at both ends of the strip-shaped post-treatment material.
[0009] Figure 1 is a schematic perspective view of an absorbent article equipped with a post-treatment material for absorbent articles according to an embodiment of the present invention. In the illustrated example, the absorbent article 200 is a pull-up diaper. The absorbent article 200, which is a pull-up diaper, has an outer body consisting of an outer member 210 on the wearer's abdominal side and an outer member 220 on the back side. Figure 2 is a schematic cross-sectional view of a post-treatment material for absorbent articles according to an embodiment of the present invention. In the illustrated example, the joint 30 is shown joined to the outer body's outer member 220. In the illustrated example, there is a space between the post-treatment material 100 and the outer member 220 to explain the configuration of the post-treatment material according to the embodiment of the present invention, but in actual use, the folded post-treatment material 100 and the outer body (for example, the outer member 220) may be in contact until use as a post-treatment material. In the illustrated example, the post-treatment material 100 for absorbent articles is strip-shaped and includes a resin layer 10 containing an elastomer layer and nonwoven fabric layers 20a and 20b. The nonwoven fabric layer 20a is the outermost layer of the post-treatment material 100 and has a density of 15 kg / m³. 3 ~120 kg / m 3The material includes a nonwoven fabric containing chemical fibers. Having such a laminated structure provides a post-treatment material that includes a joint configured to be weldable to the absorbent article by ultrasonic welding or heat welding. Furthermore, if this nonwoven fabric is the outermost surface, a post-treatment material with excellent appearance and feel can be provided. In the illustrated example, both sides of the resin layer 10 containing the elastomer layer are nonwoven fabric layers, but the nonwoven fabric layer 20b on the outer casing side of the absorbent article may be omitted. The post-treatment material 100 includes a joint 30 that is joined to the outer casing of the absorbent article (for example, the back side external member 220). In the illustrated example, the joint 30 is provided at both ends in the longitudinal direction of the post-treatment material 100. In the illustrated example, the back side external member 220 of the absorbent article 200 is a nonwoven fabric. If the outer casing is a nonwoven fabric, especially a nonwoven fabric with excellent flexibility, it may not be possible to firmly fix the post-treatment material 100 to the outer casing. If the joint 30 can be welded by ultrasonic welding or heat welding, the post-treatment material and the absorbent article can be firmly fixed even if the outer casing is made of a highly flexible nonwoven fabric. The outer casing supports an absorbent pad (not shown) on the inside (the side that comes into contact with the wearer) that absorbs excrement, etc. In the illustrated example, the post-treatment material 100 is joined to the upper part of the back-side outer member 220 (the waist portion 230 side of the absorbent article 200). The post-treatment material 100 is joined to any appropriate position on the absorbent article 200 according to its size, etc.
[0010] In the illustrated example, the post-treatment material 100 is in the shape of a strip. The strip-shaped post-treatment material 100 has two folding structures at both ends, either Z-shaped (right side in the illustrated example) or inverted Z-shaped (left side in the illustrated example). The post-treatment material 100 with folding structures offers excellent handling of absorbent articles until use, and when used for post-treatment, the post-treatment material can be unfolded and easily secured after use.
[0011] An example of a post-treatment method using a post-treatment material according to an embodiment of the present invention will be described. Figure 3 is a schematic cross-sectional view showing the form of the post-treatment material for absorbent articles when in use according to an embodiment of the present invention. In the illustrated example, during post-treatment, the folded structure of the post-treatment material 100 is unfolded by extending the portion that is not fixed to the back-side external member 220 upward (for example, in the direction opposite to the outer casing). The unfolded post-treatment material 100 and the back-side external member 220 of the outer casing form an annular structure. As described above, the post-treatment material 100 includes a resin layer 10 containing an elastomer layer. The post-treatment material 100 including the resin layer 10 containing the elastomer layer can be further extended after unfolding to extend beyond its original length. As a result, the hollow portion of the annular structure formed by the post-treatment material 100 and the back-side external member 220 can be enlarged, and the rolled absorbent article can be easily passed through the annular structure. Figure 4 is a schematic perspective view showing an absorbent article fixed with the post-treatment material for absorbent articles according to an embodiment of the present invention. Figure 5 is a schematic perspective view showing the back surface of an absorbent article fixed with the post-treatment material for absorbent articles shown in Figure 4. By ceasing the stretching of the post-treatment material 100, the stretched post-treatment material returns to its original length due to the elastic recovery of the resin layer (specifically, the elastomer layer contained in the resin layer). As a result, the rolled absorbent article can be fixed in a rolled state and easily disposed of. As shown in Figure 4, the post-treatment material 100 is joined to the back-side external member 220 by the joint 30, and even when the post-treatment material 100 is pulled to fix it, the state in which the absorbent article and the post-treatment material are joined can be maintained in good condition. Furthermore, as shown in Figure 5, on the side opposite to the joint 30, the state in which the elastically recovered post-treatment material 100 fixes the area near the center of the rolled absorbent article is maintained, which can prevent the fixed state from loosening and the internal absorbent pad from coming out to the surface, for example, when disposing of it.
[0012] The post-treatment material 100 is set to any appropriate size that can fix the absorbent article after use and fix and maintain its rolled-up state when discarded. As described above, in one embodiment, the post-treatment material 100 is in the shape of a strip. The length of the strip-shaped post-treatment material is preferably 50 mm or more, more preferably 70 mm or more, and even more preferably 100 mm or more. Also, the length of the strip-shaped post-treatment material is preferably 250 mm or less, more preferably 230 mm or less, and even more preferably 200 mm or less. In one embodiment, the length of the strip-shaped post-treatment material is preferably 50 mm to 250 mm, more preferably 70 mm to 230 mm, and even more preferably 100 mm to 200 mm. If the length of the post-treatment material is less than 50 mm, the hollow portion becomes small, which may make it difficult to fix the rolled-up absorbent article. If the length of the post-treatment material exceeds 250 mm, the productivity of the post-treatment material may decrease, resulting in high costs. The width of the post-treatment material is, for example, 8 mm or more, preferably 9 mm or more. The width of the post-treatment material is, for example, 30 mm or less, preferably 25 mm or less. In one embodiment, the width of the post-treatment material is, for example, 8 mm to 30 mm, preferably 9 mm to 25 mm. If the width of the post-treatment material is within the above range, the rolled-up absorbent article can be fixed and held in place.
[0013] The basis weight of the post-treatment material is preferably 50 g / m². 2 The above is preferable to 70 g / m². 2 The above is preferable, and more preferably 90 g / m² 2 That concludes the explanation. Furthermore, the basis weight of the post-treatment material is preferably 150 g / m². 2 The following, and more preferably 130 g / m² 2 The following, and more preferably 120 g / m² 2 The following applies: In one embodiment, the basis weight of the post-treatment material is 50 g / m². 2 ~150g / m 2 More preferably 70 g / m 2 ~130g / m 2 And more preferably 90 g / m² 2 ~120g / m 2 The basis weight of the post-treatment material is 50 g / m². 2If the basis weight is less than 150 g / m², the strength of the post-treatment material may not be sufficient. Furthermore, the productivity of the post-treatment material may decrease. 2 If it exceeds this amount, it can result in high costs.
[0014] The elongation at break of the post-treatment material is preferably 150% or more, more preferably 170% or more, and even more preferably 180% or more. Furthermore, the elongation at break of the post-treatment material is preferably 600% or less, more preferably 580% or less, and even more preferably 560% or less. In one embodiment, the elongation at break of the post-treatment material is preferably 150% to 600%, more preferably 170% to 580%, and even more preferably 180% to 560%. If the elongation at break is within the above range, the post-treatment material can be easily unfolded and stretched, and the absorbent article can be easily fixed. In this specification, elongation at break refers to the elongation at break when a sample cut to a width of 10 mm and a length of 10 cm such that the longer side is perpendicular to the flow direction of the post-treatment material is set in a tensile testing machine with a chuck distance of 50 mm and pulled at a tensile speed of 500 mm / min until it breaks.
[0015] The maximum strength of the post-treatment material is preferably 2N / 10mm or more, more preferably 3N / 10mm or more, and even more preferably 4N / 10mm or more. If the maximum strength is within the above range, damage to the post-treatment material during post-treatment can be suppressed. The higher the breaking strength of the post-treatment material, the better, for example, 50N / 10mm or more. In one embodiment, the maximum strength of the post-treatment material is preferably 2N / 10mm to 50N / 10mm, more preferably 3N / 10mm to 40N / 10mm, and even more preferably 4N / 10mm to 30N / 10mm. In this specification, the maximum strength refers to the maximum strength obtained when a sample cut to a width of 10mm and a length of 10cm such that the longer side is perpendicular to the flow direction of the post-treatment material is set in a tensile testing machine with a chuck distance of 50mm, and pulled at a tensile speed of 500mm / min until it breaks.
[0016] The post-treatment material's tensile stress is preferably 0.5 N / 10 mm or more, more preferably 0.7 N / 10 mm or more, and even more preferably 0.8 N / 10 mm or more. Furthermore, the post-treatment material's tensile stress is preferably 4 N / 10 mm or less, and even more preferably 3 N / 10 mm or less. In one embodiment, the post-treatment material's tensile stress is preferably 0.5 N / 10 mm to 4 N / 10 mm, more preferably 0.7 N / 10 mm to 4 N / 10 mm, and even more preferably 0.8 N / 10 mm to 3 N / 10 mm. If the tensile stress is within the above range, the rolled absorbent article can be well maintained in a fixed state. In this specification, tensile strength refers to the stress obtained when a sample cut to a width of 10 mm and a length of 10 cm, with the longer side perpendicular to the flow direction of the post-treated material, is set on a tensile testing machine with a chuck distance of 50 mm, stretched at a tensile speed of 500 mm / min until 100% elongation is achieved, held for 10 minutes, and then returned to the original chuck distance.
[0017] The 2N load elongation of the post-treatment material is preferably 30% or more, more preferably 35% or more, and even more preferably 40% or more. Furthermore, the 2N load elongation is preferably 200% or less, more preferably 150% or less, and even more preferably 100% or less. In one embodiment, the 2N load elongation of the post-treatment material is 30% to 200%, more preferably 35% to 150%, and even more preferably 40% to 100%. If the 2N load elongation is within the above range, the post-treatment material can be easily unfolded, and the absorbent article can be easily fixed. In this specification, the 2N load elongation refers to the elongation when a sample cut to a width of 10 mm and a length of 10 cm such that the longer side is perpendicular to the flow direction of the post-treatment material is set in a tensile testing machine with a chuck distance of 50 mm, and stretched until the load reaches 2N at a tensile speed of 500 mm / min.
[0018] The thickness of the post-treatment material can be set to any appropriate value. Preferably, the thickness of the post-treatment material is 0.5 mm or more, more preferably 0.7 mm or more, and even more preferably 0.8 mm or more. Also, preferably, the thickness of the post-treatment material is 2 mm or less, more preferably 1.5 mm or less, and even more preferably 1.2 mm or less. In one embodiment, the thickness of the post-treatment material is preferably 0.5 mm to 2 mm, more preferably 0.7 mm to 1.5 mm, and even more preferably 0.8 mm to 1.2 mm. Having a thickness within the above range makes it suitable for use as a component of absorbent articles. In this specification, the thickness of the post-treatment material refers to the value measured by taking a cross-section of the post-treatment material using a digital microscope (for example, the "VHX-1000" digital microscope manufactured by Keyence Corporation) and measuring it with image analysis software. In thickness measurement, if the outermost surface of the post-treatment material is a nonwoven fabric, parallel lines that intersect with the fibers at 10 points on the cross-section of the nonwoven fabric side (either the upper or lower part of the post-treatment material) are defined as the upper and lower edges, respectively, and the length between the upper and lower edges is defined as the thickness of the post-treatment material.
[0019] B. Non-woven layer The nonwoven fabric layer is the outermost layer of the post-treatment material. The nonwoven fabric layer has a density of 15 kg / m³. 3 ~120 kg / m 3 It includes nonwoven fabrics containing chemical fibers. Preferably, the density is 15 kg / m³. 3 ~120 kg / m 3 The nonwoven fabric containing chemical fibers forms the outermost surface of the post-treatment material. This nonwoven fabric has excellent flexibility and feel, and when bonded to an absorbent article, it blends well with the nonwoven fabric used for the outer casing of the absorbent article, resulting in a superior appearance. The nonwoven fabric layer may be a single layer or a laminate of two or more layers. In the case of a laminate of two or more layers, the nonwoven fabric forming the outermost surface has a density of 15 kg / m³. 3 ~120 kg / m 3 Any nonwoven fabric containing synthetic fibers will suffice.
[0020] The nonwoven fabric is preferably a spunlace nonwoven, carded nonwoven, air-through nonwoven, or spunjet nonwoven. Such nonwoven fabrics have excellent surface appearance and can be well-suited to the outer covering of absorbent articles.
[0021] As described above, the nonwoven fabric is a nonwoven fabric containing chemical fibers. If the nonwoven fabric is made of chemical fibers, it can be well bonded to the outer casing of absorbent articles by ultrasonic welding or heat welding. Examples of raw materials for chemical fibers include olefins such as polypropylene and polyethylene, polyesters such as polyethylene terephthalate, polyamides, polyurethanes, rayon, nylon, acrylics, copolymers thereof, or blends thereof. Preferably, olefin-based resin fibers such as polypropylene and polyethylene can be used, and more preferably polypropylene-based resin fibers are used. If the nonwoven fabric contains olefin-based resin fibers, chemical odors can be suppressed and it can be well bonded to the outer casing of absorbent articles.
[0022] The nonwoven fabric preferably contains polypropylene resin fibers in an amount of 30% by weight or more, more preferably 45% by weight or more, and even more preferably 80% by weight or more, of the fibers constituting the nonwoven fabric. The nonwoven fabric may also contain 100% by weight of polypropylene resin fibers as the fibers constituting the nonwoven fabric. In one embodiment, the nonwoven fabric contains polypropylene resin fibers in an amount of 30% to 100% by weight, more preferably 45% to 100% by weight, and even more preferably 80% to 100% by weight, of the fibers constituting the nonwoven fabric. If the content of polypropylene resin fibers is within the above range, chemical odors can be suppressed and good bonding can be achieved with the outer casing of absorbent articles.
[0023] The fibers constituting the nonwoven fabric may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include other polymers, tackifiers, plasticizers, degradation inhibitors, pigments, dyes, antioxidants, antistatic agents, lubricants, foaming agents, heat stabilizers, light stabilizers, inorganic fillers, and organic fillers. These may be present individually or in combination of two or more. The content of the other components is preferably 10% by weight or less, more preferably 7% by weight or less, even more preferably 5% by weight or less, particularly preferably 2% by weight or less, and most preferably 1% by weight or less.
[0024] The density of the nonwoven fabric is 15 kg / m². 3 ~120 kg / m 3 Preferably, the density of the nonwoven fabric is 20 kg / m³. 3 The above is preferable to 23 kg / m³. 3 That concludes the explanation. Furthermore, the density of the nonwoven fabric is preferably 115 kg / m². 3 The following, and more preferably 110 kg / m³ 3 The following applies: If the density of the nonwoven fabric is within the above range, a post-treatment material with excellent appearance and feel can be obtained. In one embodiment, the density of the nonwoven fabric is preferably 20 kg / m³. 3 ~115 kg / m 3 More preferably, 23 kg / m 3 ~110 kg / m 3 In this specification, the density of the nonwoven fabric (kg / m³) 3 ) is the basis weight (Xg / m²) of the nonwoven fabric. 2 This refers to a value calculated from the density (kg / m³) of the nonwoven fabric and the thickness (Y mm) of the nonwoven fabric, which is measured based on the method described later. More specifically, it refers to the density (kg / m³) of the nonwoven fabric. 3 ) is X / Y (kg / m 3 It is calculated as follows: Method for measuring the thickness of nonwoven fabric: A digital microscope (for example, the "VHX-1000" digital microscope manufactured by Keyence Corporation) is used to photograph the cross-section of the post-processed material, and the thickness of the nonwoven fabric is measured using image analysis software. When measuring the thickness, if the resin layer and the nonwoven fabric are in contact, the boundary between the resin layer and the nonwoven fabric is used. If the nonwoven fabrics are in contact with each other, parallel lines are drawn at the top and bottom of the cross-section of the nonwoven fabric, with 10 points of intersection with the fibers, and these lines are defined as the top and bottom edges, respectively. The length between the top and bottom edges is defined as the thickness of the nonwoven fabric.
[0025] The basis weight of the nonwoven fabric is preferably 15 gsm (g / m²). 2 The basis weight of the nonwoven fabric is preferably 50 gsm or less, more preferably 45 gsm or less, and even more preferably 40 gsm or less. In one embodiment, the basis weight of the nonwoven fabric is 15 gsm to 50 gsm, more preferably 20 gsm to 45 gsm, and even more preferably 25 gsm to 40 gsm. The basis weight of the nonwoven fabric can be measured by any suitable method. For example, it can be measured by the following method: lay the nonwoven fabric over 100 cm². 2 The weight of the cut sample was measured using an electronic balance, and the result was g / m 2 By converting to units (gsm), the basis weight of nonwoven fabrics can be measured.
[0026] C. Resin layer containing elastomer layer The resin layer containing the elastomer layer may consist only of the elastomer layer, or it may be a laminate of the elastomer layer and other resin layers. The other resin layers can be made of any suitable resin, for example, a non-elastomer resin. In one embodiment, the resin layer has a three-layer structure consisting of an elastomer layer and surface layers disposed on both sides of the elastomer layer.
[0027] The elastomer layer is formed using any suitable elastomer resin. Examples of elastomer resins that serve as the main component of the elastomer layer include olefin-based elastomers, styrene-based elastomers, vinyl chloride-based elastomers, urethane-based elastomers, ester-based elastomers, and amide-based elastomers. Preferably, olefin-based elastomers or styrene-based elastomers are used.
[0028] By using olefin-based elastomers, the post-treatment material and the outer casing can be bonded well, and chemical odors from the post-treatment material can be suppressed. Examples of olefin-based elastomers include olefin block copolymers, olefin random copolymers, ethylene copolymers, propylene copolymers, ethylene olefin block copolymers, propylene olefin block copolymers, ethylene olefin random copolymers, propylene olefin random copolymers, ethylene propylene random copolymers, ethylene (1-butene) random copolymers, ethylene (1-pentene) olefin block copolymers, ethylene (1-hexene) random copolymers, ethylene (1-heptene) olefin block copolymers, ethylene (1-octene) olefin block copolymers, ethylene (1-nonene) olefin block copolymers, ethylene (1-decene) olefin block copolymers, propylene ethylene olefin block copolymers, ethylene (α-olefin) copolymers, ethylene (α-olefin) random copolymers, ethylene (α-olefin) block copolymers, amorphous polypropylene, combinations of these with polyethylene (LLDPE, LDPE, HDPE, etc.), combinations of these with polypropylene, or combinations of these. Olefin-based elastomers may be used individually or in combination of two or more types.
[0029] The density of the olefin-based elastomer is preferably 0.830 g / cm³. 3 The above, and more preferably 0.835 g / cm³ 3 The above, and more preferably 0.840 g / cm³3 The above is the most preferred value, and most preferably it is 0.845 g / cm³. 3 That concludes the explanation. Furthermore, the density of the olefin-based elastomer is preferably 0.90 g / cm³. 3 The following, and more preferably 0.89 g / cm³ 3 The following, and more preferably 0.88 g / cm³ 3 The following applies: In one embodiment, the density of the olefin elastomer is preferably 0.830 g / cm³. 3 ~0.90g / cm 3 More preferably, 0.835 g / cm³ 3 ~0.89 g / cm³ 3 And more preferably 0.840 g / cm³ 3 ~0.89g / m 3 The concentration is preferably 0.845 g / cm³. 3 ~0.88 g / cm³ 3 Therefore, by having a density within the above range, it is possible to provide a post-treatment material for absorbent articles that can fix and maintain the rolled-up state of absorbent articles when discarded. Furthermore, thermal stability and storage stability may be improved. In addition, the manufacturing process for the elastomer layer can be simplified, and processing costs can be further reduced.
[0030] The melt flow rate (MFR) of the olefin-based elastomer at 230°C and 2.16 kgf is preferably 1.0 g / 10 min or more, more preferably 2.0 g / 10 min or more. Furthermore, the MFR of the olefin-based elastomer at 230°C and 2.16 kgf is preferably 25.0 g / 10 min or less, more preferably 23.0 g / 10 min or less, 21.0 g / 10 min or less, particularly preferably 20.0 g / 10 min or less, and most preferably 19.0 g / 10 min or less. In one embodiment, the MFR of the olefin-based elastomer at 230°C and 2.16 kgf is preferably 1.0 g / 10 min to 25.0 g / 10 min, more preferably 2.0 g / 10 min to 23.0 g / 10 min, even more preferably 2 g / 10 min to 21.0 g / 10 min, particularly preferably 2.0 g / 10 min to 20 g / 10 min, and most preferably 2.0 g / 10 min to 19.0 g / 10 min. Having the MFR within this range provides a post-treatment material for absorbent articles that can fix and maintain the rolled-up state of the absorbent article during disposal. Furthermore, thermal stability and storage stability can be improved. Additionally, the manufacturing process for the elastomer layer can be simplified, further reducing processing costs.
[0031] Preferably, an α-olefin elastomer is used as the olefin elastomer. More preferably, at least one selected from ethylene elastomer, propylene elastomer, and 1-butene elastomer is used. By adopting such an α-olefin elastomer as the olefin elastomer, it is possible to provide a post-treatment material for absorbent articles that can fix and maintain the rolled-up state of absorbent articles when discarded. Furthermore, thermal stability and storage stability can be improved. In addition, the manufacturing process for the elastomer layer and resin layer can be simplified, and processing costs can be further reduced.
[0032] Commercially available α-olefin elastomers may be used. Examples of commercially available products include the "Toughmer" (registered trademark) series from Mitsui Chemicals, Inc. (e.g., Toughmer PN-2070, Toughmer PN-3560, etc.) and the "Vistamaxx" (registered trademark) series from ExxonMobil Corporation (e.g., Vistamax 3000, Vistamax 6202, Vistamax 7010, etc.).
[0033] The α-olefin elastomer is preferably manufactured using a metallocene catalyst. The α-olefin elastomer manufactured using a metallocene catalyst can provide a post-treatment material that can fix and maintain the rolled-up state of absorbent articles during disposal. Furthermore, thermal stability and storage stability may be improved. Additionally, the manufacturing process for the elastomer layer can be simplified, further reducing processing costs.
[0034] Examples of styrene-based elastomers include SIS-based elastomers and SBS-based elastomers. Furthermore, SIS-based elastomers with specific molecular structures may be used as styrene-based elastomers. Specifically, SIS-based elastomers include those containing styrene-isoprene-styrene block copolymer molecular structures with different terminal styrene block chain lengths (hereinafter also referred to as specific SIS-based elastomers). By using such SIS-based elastomers, it is possible to provide a post-treatment material that can fix and maintain the rolled-up state of absorbent articles during disposal, and also offers a superior feel. Specific SIS-based elastomers may be used individually or in combination of two or more types.
[0035] Examples of specific SIS-based elastomers include the product name "Quintac3390 (SL-159)" (styrene content = 48% by weight) manufactured by Nippon Zeon Co., Ltd., and "Quinta One example is "c3620" (styrene content = 14% by weight).
[0036] The MFR of the specific SIS-based elastomer at 200°C and 5 kgf is preferably 5.0 g / 10 min or more, more preferably 6.0 g / 10 min or more, and even more preferably 8.0 g / 10 min or more. Furthermore, the MFR of the specific SIS-based elastomer is preferably 25.0 g / 10 min or less, more preferably 23.0 g / 10 min or less, even more preferably 21.0 g / 10 min or less, particularly preferably 20.0 g / 10 min or less, and most preferably 18.0 g / 10 min or less. In one embodiment, the MFR of a specific SIS elastomer at 200°C and 5 kgf is preferably 5.0 g / 10 min to 25.0 g / 10 min, more preferably 6.0 g / 10 min to 23.0 g / 10 min, even more preferably 8.0 g / 10 min to 21.0 g / 10 min, particularly preferably 8.0 g / 10 min to 20.0 g / 10 min, and most preferably 8.0 g / 10 min to 18.0 g / 10 min. Having the MFR within this range allows for the fixed and maintained rolled state of absorbent articles during disposal, and provides a post-treatment material with superior texture. Furthermore, the manufacturing process for the elastomer layer can be simplified, allowing for further reduction of processing costs.
[0037] The content of the elastomer resin, which is the main component in the elastomer layer, is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more. Furthermore, the content of the elastomer resin, which is the main component, is preferably 100% by weight or less, and more preferably 95% by weight or less. By having the content of the elastomer resin, which is the main component, within the above range, the elastomer layer can exhibit sufficient elastomer properties.
[0038] The elastomer layer may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include other polymers, tackifiers, plasticizers, degradation inhibitors, pigments, dyes, antioxidants, antistatic agents, lubricants, foaming agents, heat stabilizers, light stabilizers, inorganic fillers, and organic fillers. These may be present individually or in combination of two or more. The content of the other components in the elastomer layer is preferably 10% by weight or less, more preferably 7% by weight or less, even more preferably 5% by weight or less, particularly preferably 2% by weight or less, and most preferably 1% by weight or less.
[0039] Any suitable polymer can be used as the other polymer. For example, a non-elastomer resin used in the surface layer described later can be used. The non-elastomer resin can be used in any suitable amount. For example, the content of the non-elastomer resin in the elastomer resin is 50% by weight or less, and the total content of the non-elastomer resin and the elastomer resin is 100% by weight.
[0040] The thickness of the elastomer layer is preferably 20 μm or more, more preferably 30 μm or more. Furthermore, the thickness of the elastomer layer is preferably 200 μm or less, more preferably 160 μm or less, even more preferably 140 μm or less, particularly preferably 120 μm or less, and most preferably 100 μm or less. In one embodiment, the thickness of the elastomer layer is preferably 20 μm to 200 μm, more preferably 20 μm to 160 μm, even more preferably 30 μm to 140 μm, particularly preferably 30 μm to 120 μm, and most preferably 30 μm to 100 μm. If the thickness of the elastomer layer is within this range, it becomes possible to provide a post-processing material that can fix and maintain the rolled-up state of absorbent articles during disposal.
[0041] The elastomer layer may be a single layer or two or more layers. If it is a laminate of two or more layers, it may have multiple layers made of the same elastomer or multiple layers made of different elastomers.
[0042] In one embodiment, the resin layer is composed of three layers. In this embodiment, the resin layer is composed of an intermediate layer and surface layers arranged on both sides of the intermediate layer. Preferably, the intermediate layer contains a white pigment. By including a white pigment, an appearance suitable for sanitary products can be obtained.
[0043] When the resin layer consists of three layers, at least one of the surface layer and intermediate layer may be made of the elastomer described above. The surface layers on both sides of the intermediate layer may be made of elastomer resin, or the surface layers on both sides may be made of non-elastomer resin, or one side of the intermediate layer may have a surface layer made of elastomer resin and the other side may have a surface layer made of non-elastomer resin. By making the surface layer out of elastomer resin, the extensibility of the post-treatment material is improved, making it easier to fix and maintain the rolled state of sanitary products when disposing of them. As a result, disposal of sanitary products becomes easier. By making the surface layer out of non-elastomer resin, blocking when the resin layer is made into a wound body can be suppressed. In addition, the processability (slitting ability) of the resin layer can be improved. Preferably, the intermediate layer is made of elastomer resin, and the surface layers on both sides of the intermediate layer are made of non-elastomer resin.
[0044] Any suitable resin can be used as the non-elastomer resin. In this specification, a non-elastomer resin refers to a resin other than the elastomer resin described above. Preferably, a non-elastomer olefin resin is used as the non-elastomer resin.
[0045] Examples of non-elastomer olefin resins include α-olefin homopolymers, copolymers of two or more α-olefins, block polypropylene, random polypropylene, and copolymers of one or more α-olefins with other vinyl monomers. Examples of copolymerization forms in copolymers include block form and random form.
[0046] Examples of α-olefins include α-olefins having 2 to 12 carbon atoms. Examples of such α-olefins include ethylene, propylene, 1-butene, and 4-methyl-1-pentene.
[0047] Examples of α-olefin homopolymers include polyethylene (PE), homopolypropylene (PP), poly(1-butene), and poly(4-methyl-1-pentene). Examples of polyethylene (PE) include low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), medium-density polyethylene (MDPE), and high-density polyethylene (HDPE). The structure of homopolypropylene (PP) may be isotactic, atactic, or syndiotactic.
[0048] Examples of copolymers of two or more types of α-olefins include ethylene / propylene copolymer, ethylene / 1-butene copolymer, ethylene / propylene / 1-butene copolymer, ethylene / α-olefin copolymer with 5 to 12 carbon atoms, and propylene / α-olefin copolymer with 5 to 12 carbon atoms.
[0049] Examples of copolymers of one or more α-olefins with other vinyl monomers include ethylene / vinyl acetate copolymers, ethylene / alkyl acrylate copolymers, ethylene / alkyl methacrylate copolymers, and ethylene-non-conjugated diene copolymers.
[0050] Preferably, non-elastomer olefin resins used are HDPE, LDPE, LLDPE, homopolypropylene (h-PP), block polypropylene (b-PP), random polypropylene (r-PP), and mixtures thereof. By using these resins, blocking can be suppressed when the resin layer is wound into a coiled body. Furthermore, the processability (slitting ability) of the resin layer can be improved. In addition, chemical odors from post-treatment materials can be suppressed. Moreover, good bonding can be achieved with the outer casing of absorbent articles.
[0051] In one embodiment, a propylene resin is preferably used as the non-elastomer resin, and more preferably random polypropylene is used. The content of random polypropylene in the non-elastomer resin is preferably 50% by weight or more, more preferably 70% by weight or more, and even more preferably 90% by weight or more.
[0052] The olefin resin layer may contain any other suitable components as long as they do not impair the effects of the present invention. Examples of such other components include mold release agents, UV absorbers, heat stabilizers, fillers, lubricants, colorants (such as dyes), antioxidants, eye discharge inhibitors, antiblocking agents, foaming agents, polyethyleneimine, and the like. These may be present individually or in combination of two or more. The content of the other components in the olefin resin layer is preferably 10% by weight or less, more preferably 7% by weight or less, even more preferably 5% by weight or less, particularly preferably 2% by weight or less, and most preferably 1% by weight or less.
[0053] When the elastomer layer has an intermediate layer and a surface layer, the thicknesses of the intermediate layer and the surface layer can be set to any appropriate value such that the thickness of the elastomer layer is within the above range. The thickness of the intermediate layer is preferably 18 μm or more, more preferably 28 μm or more. Also, the thickness of the intermediate layer is preferably 94 μm or less, more preferably 56 μm or less, and even more preferably 46 μm or less. In one embodiment, the thickness of the intermediate layer is preferably 18 μm to 94 μm, more preferably 28 μm to 56 μm. The thickness of the surface layer is preferably 1 μm or more. Also, the thickness of the surface layer is preferably 4 μm or less, more preferably 3 μm or less, and even more preferably 2 μm or less. In one embodiment, the thickness of the surface layer is preferably 1 μm to 4 μm, more preferably 1 μm to 3 μm, and even more preferably 1 μm to 2 μm. The thicknesses of the surface layers located on both sides of the intermediate layer can preferably be set to the same thickness.
[0054] D. Joint The joint is a portion that can be welded by ultrasonic welding or heat welding. If the joint can be welded by ultrasonic welding or heat welding, the post-treatment material and the absorbent article can be firmly joined, even when a flexible nonwoven fabric is used as the outer covering of the absorbent article. In addition, by not using adhesives or glues, the manufacturing process can be reduced, and the environmental burden from chemical substances can be reduced. For example, a post-treatment material consisting of a nonwoven fabric layer containing chemical fibers and a resin layer containing an elastomer layer can be a post-treatment material that includes a joint.
[0055] The joint is typically formed at both ends of the strip-shaped post-treatment material in the longitudinal direction. The joint can be set to any appropriate size (area). The area of the joint is preferably 25 mm². 2 The above is more preferable to 30 mm 2 That is all. Furthermore, the area of the joint is preferably 200 m². 2 The following, more preferably 100m 2 The following applies: In one embodiment, the area of the joint is preferably 25 mm². 2~200mm 2 And more preferably 30 mm 2 ~100mm 2 Therefore, if the size of the joint is within the above range, the post-treatment material and the absorbent article can be firmly joined, and the detachment of the post-treatment material from the absorbent article during post-treatment can be suppressed. In the case of joining by an embossed pattern as described later, it is sufficient if the size of the area where the embossed pattern is formed is within the above range.
[0056] The joint may be joined over its entire surface, or it may be a joint having an embossed pattern. The embossed pattern can be any suitable shape. Specific examples of embossed patterns include, for example, a continuous grid, a discontinuous grid, a continuous curve, a discontinuous curve, a continuous zigzag, a discontinuous zigzag, a continuous straight line, a discontinuous straight line, a circular shape (e.g., dots), an ellipse, a hollow circle, a hollow ellipse, an arc, and a hollow arc.
[0057] The ratio of the area of the welded portion due to the embossed pattern to the total area of the joint (hereinafter sometimes referred to as the "embossed welded area ratio") is preferably 10% or more, more preferably 15% or more, even more preferably 20% or more, and particularly preferably 30% or more. Furthermore, the welded area ratio is preferably 100% or less, more preferably 80% or less, even more preferably 60% or less, and particularly preferably 50% or less. In one embodiment, the embossed welded area ratio is preferably 10% to 100%, more preferably 15% to 80%, even more preferably 20% to 60%, and particularly preferably 30% to 50%. If the embossed welded area ratio is within the above range, the post-treatment material and the absorbent article can be firmly joined, and the detachment of the post-treatment material from the absorbent article during post-treatment can be suppressed.
[0058] The embossing depth and the thickness of the welded area due to the embossing pattern can be set to any appropriate value. For example, the embossing depth is 0.1 mm to 2.0 mm. The thickness of the welded area due to the embossing pattern is, for example, 100 μm or less.
[0059] D-1.Ultrasonic welding Ultrasonic bonding can be performed by any suitable method. Forming a joint using ultrasonic bonding allows for a stronger bond between the post-treatment material and the absorbent article. Furthermore, the generation of distinctive odors from adhesives and sealants is suppressed, reducing the environmental impact of adhesives and sealants. Additionally, the number of manufacturing steps can be reduced.
[0060] Ultrasonic welding is performed by placing the members to be joined (e.g., a post-treatment material and an absorbent article's outer casing) between a component that emits vibrational energy using ultrasound (generally called a "horn") and a roll-shaped component (generally called an "anvil"). Typically, the horn is positioned vertically above the members to be joined and the anvil. The horn vibrates, usually at 20,000 Hz to 40,000 Hz, transferring energy to the members to be joined under pressure, usually in the form of frictional heat. The frictional heat and pressure soften or melt a portion of at least one of the members to be joined, thereby joining the layers together.
[0061] The pressing force between the horn and anvil in ultrasonic welding is preferably 100N to 1500N, more preferably 300N to 1300N, even more preferably 500N to 1100N, and particularly preferably 700N to 1000N. By having the pressing force between the horn and anvil within this range, flexibility can be further improved, resulting in a better tactile feel. Furthermore, production speed can be increased.
[0062] In one embodiment, ultrasonic welding is performed in a manner commonly known as "continuous ultrasonic welding." Continuous ultrasonic welding is typically used to seal members to be joined, which can be supplied into the welding apparatus substantially continuously. In continuous ultrasonic welding, the horn is usually fixed, and the members to be joined move directly beneath it. One type of continuous ultrasonic welding uses a fixed horn and a rotating anvil surface. During continuous ultrasonic welding, the members to be joined are pulled between the horn and the rotating anvil. The horn usually extends longitudinally toward the members to be joined, and vibrations travel axially along the horn to the material.
[0063] In another embodiment, the horn is of a rotating type, cylindrical in shape and rotating about a longitudinal axis. The input vibration is in the axial direction of the horn, and the output vibration is in the direction of radiation of the horn. The horn is positioned in close proximity to the anvil, which can also rotate such that the members to be joined pass between the cylindrical surfaces at a linear velocity substantially equal to the tangential velocity of the cylindrical surfaces.
[0064] Ultrasonic fusion bonding is described, for example, in Japanese Patent Publication No. 2008-526552, Japanese Patent Publication No. 2010-195044, Japanese Patent Publication No. 2013-231249, Japanese Patent Publication No. 2015-16294, and U.S. Patent No. 5,976,316, the disclosures thereof which are incorporated herein by reference.
[0065] In one embodiment, the surface of the rotating anvil preferably has an embossed pattern. Specific examples of such embossed patterns are as described above. Embossed patterns of rotating anvil surfaces are disclosed, for example, in Japanese Patent Application Publication No. 2017-65253, which is incorporated herein by reference.
[0066] The shape of the tip portion of the protrusions constituting the embossed pattern (the portion that contacts the member to be joined) can be any suitable shape, for example, circular. When using an embossed pattern with a circular tip portion, the diameter of the circular portion is preferably 0.4 mm or more, more preferably 0.45 mm or more, and even more preferably 0.5 mm or more. Also, the diameter of the circular portion is preferably 1 mm or less, more preferably 0.9 mm or less, and even more preferably 0.8 mm or less. By having the diameter within the above range, it is possible to achieve both productivity of post-treatment material and adhesive strength. The embossing depth is preferably 0.5 mm or more. Also, the embossing depth is preferably 1.5 mm or less, and even more preferably 1 mm or less. By having the embossing depth within the above range, it is possible to achieve both productivity of post-treatment material and adhesive strength.
[0067] Furthermore, from the viewpoint of stabilizing the quality of the resulting post-processed material, it is preferable to adjust the anvil temperature to an appropriate temperature and perform ultrasonic welding. If the anvil temperature varies too much, variations in adhesive strength will occur, resulting in the problem of not being able to obtain a post-processed material of stable quality. The anvil temperature can be set, for example, to 5°C to 90°C in absolute temperature, and the temperature is adjusted so that the anvil temperature is within ±5°C of the set temperature. By keeping the anvil temperature within the above range, it is possible to prevent a decrease in productivity due to condensation, etc., and to prevent adverse effects on product characteristics such as hardening of the resin layer including the nonwoven fabric and elastomer layer.
[0068] D-2. Heat welding joining Joining by heat welding can be carried out by any suitable method. For example, the heat-welded portion can be formed by forming the joint using a heated embossed pattern roll. The heating temperature is preferably 150°C to 220°C, more preferably 160°C to 210°C, and even more preferably 170°C to 200°C.
[0069] E. Method for manufacturing post-treatment materials Post-processing materials can be manufactured by any suitable method. For example, (1) a method of laminating a resin layer containing an elastomer layer formed by extruding from a T-die of an extruder with a nonwoven fabric layer drawn separately from a roll body, (2) a method of simultaneously extruding and laminating a resin layer containing an elastomer layer and a nonwoven fabric layer, (3) a method of bonding a resin layer containing an elastomer layer and a nonwoven fabric layer, each prepared separately, with an adhesive, and (4) thermal lamination and ultrasonic bonding of the resin layer containing an elastomer layer and the nonwoven fabric layer. Preferably, the bonding method is ultrasonic bonding (ultrasonic fusion bonding). With ultrasonic bonding, since no adhesive is used, the process of forming an adhesive layer can be omitted, and carbon dioxide emissions can be reduced. Furthermore, the thermal lamination and ultrasonic bonding methods described above can reduce the environmental burden from chemical substances and reduce contamination of other materials during the manufacturing stage.
[0070] In one embodiment of the present invention, the resin layer including the nonwoven fabric layer and the elastomer layer is joined via an appropriate adhesive. Preferably, a hot-melt adhesive is used. By using a hot-melt adhesive, the need to add a tackifier as a component of the resin layer is reduced, for example, extrusion stability is improved and the problem of the tackifier adhering to the molding roll can be suppressed. In addition, problems of contamination of the manufacturing line due to volatile matter contamination caused by the tackifier can be suppressed.
[0071] The hot melt adhesive may be applied to the entire surface of the nonwoven fabric layer or to a portion of the nonwoven fabric layer. When applying the hot melt adhesive to a portion of the nonwoven fabric layer, it is preferable that the hot melt adhesive is applied so that it includes at least the edges of the nonwoven fabric layer. The hot melt adhesive can be applied to the nonwoven fabric and / or resin layer by any suitable method.
[0072] Any suitable adhesive can be used as the hot melt adhesive. Examples include hot melt adhesives containing styrene elastomers and hot melt adhesives containing olefin polymers. Preferably, the hot melt adhesive contains a styrene polymer. Examples of such styrene polymers include those containing SIS, those containing SBS, their respective hydrogenated products, and blends thereof. The hot melt adhesive may be used alone or in combination of two or more types. Furthermore, if the hot melt adhesive contains a styrene polymer, the styrene polymer may be of one type or two or more types. When the hot melt adhesive contains a styrene polymer, the content of the styrene polymer in the hot melt adhesive is preferably 10% to 90% by weight.
[0073] The hot melt adhesive may further contain any other suitable components. Examples of such other components include liquid paraffin, tackifiers, antioxidants, UV absorbers, light stabilizers, and fluorescent agents. These other components may be present individually or in combination of two or more. These other components are used in any appropriate amount.
[0074] The post-processing material may undergo further activation treatment after lamination. The activation treatment can be carried out by any suitable method. Specifically, this may include stretching the post-processing material in the width direction and / or length direction, as well as mechanically destroying the fiber structure in a portion of the nonwoven fabric layer. The activated post-processing material has improved elongation, making it easier to post-process the rolled absorbent material.
[0075] F. Absorbent articles The absorbent article of the embodiment of the present invention comprises an outer casing and the above-mentioned post-treatment material. By providing the above-mentioned post-treatment material, it is possible to provide an absorbent article that can be easily processed. Examples of absorbent articles include pant-type diapers, tape-type diapers, sanitary napkins, etc. Pant-type diapers are preferred. The absorbent article that is a pant-type diaper will be described in detail below.
[0076] The structure of a pant-type diaper is not particularly limited, and any known structure can be used. An example of a pant-type diaper is one that comprises an absorbent pad and an outer body having a pant-like shape that supports the absorbent pad on its inner surface. The absorbent pad comprises at least a liquid-permeable top sheet, a liquid-impermeable back sheet, and an absorbent body disposed between them that absorbs and retains bodily fluids that have permeated through the top sheet. The outer body is divided into, for example, an ventral outer member that mainly contacts the wearer's abdomen, a dorsal outer member that mainly contacts the wearer's back, and a crotch member interposed between the ventral and dorsal outer members, mainly contacting the wearer's crotch, and mainly supporting the absorbent pad. The dorsal outer member may be composed of multiple parts. Examples of parts constituting the dorsal outer member include a back sheet outer member and a waist outer member. The post-treatment material may be joined to the back sheet outer member or to the waist outer member. Furthermore, one end of the post-processing material may be joined to the backsheet external member, and the other end to the waist external member. An example of an outer body is one which has side seal portions that join the widthwise edges of the ventral external member and the dorsal external member, and has a waist opening and a pair of leg openings in the widthwise direction. Here, the ventral external member and the dorsal external member may be substantially symmetrical with respect to the crotch member.
[0077] Preferably, the outermost surface of the outer casing is a nonwoven fabric, and more preferably, has a density of 15 kg / m³. 3 ~120 kg / m 3 This is a nonwoven fabric. When such a nonwoven fabric is the outermost surface of the outer packaging, it is possible to provide an absorbent article with a pleasant feel and excellent flexibility. Preferably, the density of the nonwoven fabric is 20 kg / m³. 3 The above is preferable to 23 kg / m³. 3 That concludes the explanation. Furthermore, the density of the nonwoven fabric is preferably 115 kg / m². 3 The following, and more preferably 110 kg / m³ 3The following applies: If the density of the nonwoven fabric is within the above range, it will have excellent appearance and feel. In one embodiment, the density of the nonwoven fabric is preferably 20 kg / m³. 3 ~115 kg / m 3 More preferably, 23 kg / m 3 ~110 kg / m 3 That is the case.
[0078] The nonwoven fabric forming the outermost surface of the outer casing is preferably a spunlace nonwoven fabric, a carded nonwoven fabric, an air-through nonwoven fabric, or a spunjet nonwoven fabric. The nonwoven fabric used for the outer casing is the same as the nonwoven fabric used for the post-treatment material described above. The nonwoven fabric used for the post-treatment material and the nonwoven fabric used for the outer casing may be the same or different.
[0079] In the absorbent article of the embodiment of the present invention, the above-mentioned post-treatment material is joined by ultrasonic welding or heat welding. The method of ultrasonic welding or heat welding is as described above. [Examples]
[0080] The present invention will be specifically described below with reference to examples, but the present invention is not limited in any way to these examples. The evaluation methods in the examples are as follows. Unless otherwise specified, parts refer to parts by weight, and % refers to percentage by weight.
[0081] [Example 1] A resin layer (hereinafter also referred to as elastic film) was extruded using a 2-type, 3-layer (A layer / B layer / A layer) extrusion T-die molding machine. Specifically, 100 parts by weight of olefin resin 1 (manufactured by SCG Performance Chemicals, product name: P756C) was placed into the A layer of the extruder, 46.5 parts by weight of olefin elastomer 1 (manufactured by ExxonMobil, product name: Vistamax 6202), 46.5 parts by weight of olefin elastomer 2 (manufactured by Mitsui Chemicals, Inc., product name: Toughmer PN-3560), and 7 parts by weight of white pigment (titanium dioxide, manufactured by Ampacet, product name: White PE MB 111413) were placed into the B layer of the extruder, and elastic film 1 with a basis weight of 45 g / m2 (A layer / B layer / A layer = 4% / 92% / 4%) was extruded. The extrusion temperature was carried out under the following conditions. Layer A: 200°C, Layer B: 230°C, Die temperature: 230°C. Nonwoven fabric A (polypropylene (PP) carded type, basis weight = 24 gsm) was directly laminated to both sides of the obtained elastic film 1, and ultrasonic bonding was performed to ensure complete bonding. Ultrasonic bonding was performed using an ultrasonic fusion equipment (Herrmann, equipment name: MICROBOND (ULTRABOND48:20)) at a frequency of 20 kHz (output strength: 1800 W) and a line speed of 100 m / min, by ultrasonic fusion lamination in a three-layer laminated state of nonwoven fabric 1 / elastic film / nonwoven fabric 1. The embossed pattern roll used for bonding had a bonding area of 8% and a dot pattern with a diameter of 0.7 mm. After that, an activation treatment was performed to obtain post-processed material 1.
[0082] [Example 2] Post-treatment material 2 was obtained in the same manner as in Example 1, except that an elastic film was prepared using 100 parts by weight of olefin resin 1 (manufactured by SCG Performance Chemicals, product name: P756C) in the A layer of the extruder, and 46.5 parts by weight of styrene elastomer 1 (manufactured by Nippon Zeon Co., Ltd., product name: Quintac 3620), 46.5 parts by weight of styrene elastomer 2 (manufactured by Nippon Zeon Co., Ltd., product name: Quintac 3390), and 7 parts by weight of white pigment (titanium dioxide, manufactured by Ampacet, product name: White PE MB 111413) in the B layer of the extruder.
[0083] [Example 3] Post-treatment material 3 was obtained in the same manner as in Example 2, except that the elastic film and the nonwoven fabric were heat-sealed together. The heat-sealing was performed by heat-seal lamination in a three-layer stacked state of nonwoven fabric 1 / elastic film / nonwoven fabric 1 at a processing temperature of 200°C, a linear pressure of 160 N / mm, and a processing speed of 50 m / min. The embossed pattern roll used for fusion was a roll with a fusion area of 8% and a dot pattern with a diameter of 0.7 mm. Next, an activation treatment was performed to obtain post-treatment material 3.
[0084] [Example 4] Post-treatment material 4 was obtained in the same manner as in Example 2, except that the elastic film and nonwoven fabric were laminated with an adhesive. Lamination with adhesive was performed by bonding the nonwoven fabric 1 to both sides of the elastic film using a roll. At this time, hot melt adhesive (manufactured by Nitto Bent Vancheric, product name: AC280) was applied in a stripe pattern (adhesive width: 1 mm, spacing: 1 mm) (15 g / m²) to the bonding side of the nonwoven fabric. 2 ) was performed. Next, an activation treatment was carried out to obtain post-treatment material 4.
[0085] [Example 5] Post-treatment material 5 was obtained in the same manner as in Example 2, except that nonwoven fabric B (PP spunlace type, basis weight = 35 gsm) was laminated on one side of the elastic film instead of nonwoven fabric A.
[0086] [Example 6] A post-treatment material 6 was obtained in the same manner as in Example 2, except that nonwoven fabric B was laminated on both sides of the elastic film.
[0087] [Example 7] A post-treatment material 7 was obtained in the same manner as in Example 2, except that a nonwoven fabric C (PP-polyethylene terephthalate (PET) spunlace type (PP fiber content: 50% by weight), basis weight = 35 gsm) was laminated on both sides of the elastic film.
[0088] [Example 8] A post-treatment material 8 was obtained in the same manner as in Example 2, except that a nonwoven fabric D (PP spunlace type, basis weight = 25 gsm) was laminated on both sides of the elastic film.
[0089] (Comparative Example 1) Post-treatment material C1 was obtained in the same manner as in Example 2, except that the nonwoven fabric was not laminated (i.e., the resin layer was used alone).
[0090] (Comparative Example 2) Post-treatment material C2 was obtained in the same manner as in Example 2, except that nonwoven fabric E (PP spunbond type, basis weight = 20 gsm) was laminated on both sides of the elastic film.
[0091] (Comparative Example 3) A post-treatment material C3 was obtained in the same manner as in Example 4, except that a nonwoven fabric F (cotton spunlace type, basis weight = 35 gsm) was laminated on both sides of the elastic film.
[0092] (Comparative Example 4) We attempted to prepare a post-treatment material in the same manner as in Example 2, except that we laminated nonwoven fabric F on both sides of the elastic film, but the nonwoven fabric and the elastic film did not adhere, and we were unable to obtain a post-treatment material.
[0093] (Comparative Example 5) Post-treatment material C5 was obtained in the same manner as in Example 2, except that nonwoven fabric G (PE-PET air-through type, basis weight = 25 gsm) was used as the nonwoven fabric layer.
[0094] (Reference example) The post-treated material prepared in Example 1 had a dry thickness of 40 g / m². 2 An adhesive (manufactured by Nitto Bent Vancheric, product name: AC280) was applied to the diaper, and lamination was attempted. The post-treatment material peeled off the diaper after lamination, making it difficult to use as a post-treatment material.
[0095] [evaluation] The post-treatment materials obtained in the examples, comparative examples, and reference examples were evaluated as follows. The results are shown in Table 1.
[0096] <Tensile Test> Tensile testing was performed by subjecting the obtained post-processed material to the following tests. The post-processed material was cut into 10 mm wide and 10 cm long strips, with the longer side being in the direction perpendicular to the film flow direction (MD) (CD), to create samples. Each sample was set in a tensile testing machine (ZwickRoell, product name: Z0005 1kN) with a chuck distance of 50 mm, and pulled at a tensile speed of 500 mm / min until fracture. The maximum strength, elongation at fracture, and elongation at 2N were measured at that time. Evaluation was performed on five samples for each test, and the average value was used.
[0097] <10-minute retention test> The 10-minute holding test was evaluated by subjecting the obtained post-treatment material to the following test. The post-treatment material was cut into strips 10 mm wide and 10 cm long, with the longer side being in the direction perpendicular to the film flow direction (MD) (CD), to prepare the samples. Each sample was set on a tensile testing machine (ZwickRoell, product name: Z0005 1kN) with a chuck distance of 50 mm, and pulled at a tensile speed of 500 mm / min until 100% elongation was achieved. After holding at 100% elongation for 10 minutes, the chuck distance was returned to the original. The stress after 10 minutes (post-elongation stress) was measured. The deformation after 10 minutes was calculated by measuring the amount of deformation of the sample after holding for 10 minutes using a ruler. Evaluation was performed on five samples for each sample, and the average value was used.
[0098] <Adhesion to the diaper outer casing> The post-processed material, cut to a width of 10 mm in the MD direction, was welded using an ultrasonic welding machine (Honda Electronics Co., Ltd., product name: SONAC-37, welding fitting YK01) to a commercially available carded nonwoven fabric (24 g / m²). 2 The material was bonded to PP. When the bonded post-treatment material was pulled in the CD direction, those that did not peel off from the nonwoven fabric were marked with ○, and those that did not bond or peeled off easily were marked with ×.
[0099] <Exterior> In the above evaluation of adhesion to diapers, when laminated to nonwoven fabric, if the outermost surface of the laminate (the side visible from the outside) was made of nonwoven fabric and was soft and fluffy, it was marked as ○○; if it was made of nonwoven fabric but felt hard, it was marked as ○; and if it was made of film, it was marked as ×.
[0100] <Ease of disposal> Products with a maximum strength of 3N / 10mm or more, a breaking elongation of 150% or more, and an elongation at 2N of 65% or more were marked with ○○○, products with a maximum strength of 3N / 10mm or more, a breaking elongation of 150% or more, and an elongation at 2N of 60% or more were marked with ○○, products with a maximum strength of 3N / 10mm or more, a breaking elongation of 150% or more, and an elongation at 2N of 50% or more were marked with ○, and products with any of the above evaluations below the specified range were marked with ×.
[0101] <Retention> Tests where the stress after 10 minutes was 1 N / 10 mm or more and the deformation after 10 minutes was 50% or less were marked with a circle (○), and all other tests were marked with a cross (×).
[0102] <Nonwoven fabric thickness> Using a Keyence VHX-1000 digital microscope, cross-sections of the post-processed material were photographed at 100x magnification, and the nonwoven fabric thickness was measured using the microscope's image analysis software. For thickness measurement, when the resin layer (elastic film) and the nonwoven fabric were in contact, the boundary between the resin layer and the nonwoven fabric was used. When the nonwoven fabrics were in contact with each other, parallel lines were drawn at the top and bottom of the cross-section of the nonwoven fabric, with 10 points of intersection with the fibers, and these were defined as the top and bottom edges, respectively. The length between the top and bottom edges was defined as the nonwoven fabric thickness. The nonwoven fabric thickness was measured for 3 or more samples, and the average value was used as the nonwoven fabric thickness.
[0103] [Table 1] [Industrial applicability]
[0104] The post-treatment material for absorbent articles according to embodiments of the present invention can be used in any suitable article in which the effects of the present invention can be effectively utilized. Typical examples of absorbent articles of the present invention include diapers (pants-type diapers, tape-type diapers). [Explanation of symbols]
[0105] 100 Post-treatment material for absorbent articles 10 Resin layer containing elastomer layer 20a non-woven layer 20b Non-woven layer 200 absorbent articles
Claims
1. Density is 15 kg / m 3 ~120kg / m 3 The post-treatment material for absorbent articles includes a nonwoven fabric layer including a nonwoven fabric including chemical fibers, a resin layer including an elastomer layer, and a bonding portion to be bonded to an exterior body of an absorbent article, the nonwoven fabric layer is the outermost surface of the post-treatment material for absorbent articles, The post-treatment material for absorbent articles, wherein the joint portion is configured to be weldable by ultrasonic welding or thermal welding.
2. The post-treatment material for absorbent articles according to claim 1 , wherein the nonwoven fabric is a spunlace nonwoven fabric, a carded nonwoven fabric, an air-through nonwoven fabric, or a spunjet nonwoven fabric.
3. The post-treatment material for absorbent articles according to claim 1 , wherein the chemical fiber is an olefin-based resin fiber.
4. The post-treatment material for absorbent articles according to claim 3 , wherein the chemical fiber is a polypropylene-based resin fiber.
5. The post-treatment material for absorbent articles according to claim 4 , wherein the nonwoven fabric contains 30% by weight or more of polypropylene-based resin fibers.
6. The absorbent article post-treatment material according to claim 1 , wherein the elastomer layer comprises a styrene-based elastomer or an olefin-based elastomer.
7. The absorbent article post-treatment material according to claim 6 , wherein the elastomer layer comprises an olefin-based elastomer.
8. The post-treatment material for absorbent articles according to claim 7 , wherein the olefin-based elastomer is a propylene-based elastomer.
9. The absorbent article post-treatment material according to claim 1 , comprising a folded structure.
10. 2. The post-treatment material for absorbent articles according to claim 1, which is in a strip shape and has a length of 50 mm to 250 mm.
11. Basis weight: 50 g / m 2 ~150g / m 2 The post-treatment material for absorbent articles according to claim 1 ,
12. 2. The post-treatment material for absorbent articles according to claim 1, wherein the breaking elongation is 150% to 600%.
13. The post-treatment material for absorbent articles according to claim 1, which has a maximum strength of 2 N / 10 mm or more.
14. The post-treatment material for absorbent articles according to claim 1, which has a post-elongation stress of 0.5 N / 10 mm or more.
15. The post-treatment material for absorbent articles according to claim 1, which has an elongation at a load of 2N of 30% or more.
16. An absorbent article comprising an exterior body and the post-treatment material for absorbent articles according to any one of claims 1 to 15.
17. The outermost surface of the exterior body is a nonwoven fabric, and the density of the nonwoven fabric is 15 kg / m 3 ~120kg / m 3 17. The absorbent article of claim 16,
18. 17. The absorbent article of claim 16, which is a pant-type diaper.
19. Density is 15 kg / m 3 ~120kg / m 3 and laminating a nonwoven fabric layer including a nonwoven fabric containing a chemical fiber having the above formula (I) and a resin layer including an elastomer layer to produce a laminate. and joining the laminate to an outer casing of the absorbent article by ultrasonic welding or thermal welding.